FX intervention and domestic credit in a partially dollarized economy: Evidence using microdata from Peru. - Marcos Ceron; Rafael Nivin; Diego Yamunaque (Graduate Institute of International and Development Studies, 2023)
In this work we study the impact of FX interventions on Credit growth in Peru. Using Panel data at the firm-bank level from the Peruvian Credit Registry we find that purchases of dollars by the Central Bank are associated with reductions on the stock of credit held by Medium, Big and Corporate Firms in the Peruvian economy. We also found that the impact is stronger for firms with a higher level of debt dollarization. These results suggest that FX interventions can be seen as an additional tool for Financial stability, especially in times of large inflows of capital.
Keywords: E58; F31; F33; G20; 330; FX intervention; Credit registry; Emerging markets; Credit growth